International Editorial Board of vol. 17, 2019, Journal Scientific and Applied Research: International Editorial Board of vol. 17, 2019, Journal Scientific and Applied Research - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
International Editorial Board of vol. 17, 2019, Journal Scientific and Applied Research